IMPLEMENTASI PEMBINAAN PENGAWAS SEKOLAH DALAM MENINGKATKAN KINERJA GTK MELALUI PEMANTAUAN STANDAR PTK PADA SEKOLAH DASAR DAERAH BINAAN KECAMATAN KOPANG KABUPATEN LOMBOK TENGAH TAHUN 2022 - AHMAD AHMAD (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2022)
This study aims to improve gtk performance through monitoring ptk standards at elementary schools in the target area of ??the Kopang sub-district. The approach used in school supervision is a collaborative approach, by making the teachers and principals of the target schools work partners in achieving goals, with a personal approach of "Give-Emphatic-Own-Love (GEOL)". The results of monitoring the CAR Standards show that the overall standard fulfillment in the target schools still needs to be improved, through coordination, submission of proposals, mentoring, and collaboration with various stakeholders. The achievement of 83% (15 elementary schools) who have definitive school principals and still 17% (3 elementary schools) occupy the duties of the principal. The achievement of 38% (65 teachers) has been fulfilled through the elements of PNS and/or PPPK and there are still 28% (105 teachers) who are still honorary teachers. The education staff, which includes OPS, TAS, Librarian and school custodian, are all still honorary and totaling 20 people ABSTRAKPenelitian ini bertujuan untuk meningkatkan kinerja gtk melalui pemantauan standar ptk pada sekolah dasar daerah binaan kecamatan kopang. Pendekatan yang digunakan dalam pengawasan sekolah adalah Colaborative approach,  dengan menjadikan Guru dan Kepala Sekolah binaan sebagai mitra kerja dalam mencapai tujuan, dengan pendekatan personal “Give-Emphatic-Own-Love (GEOL)”. Hasil pemantauan Standar PTK menunjukkan, dari kesuluruhan pemenuhan standar di sekolah binaan masih perlu untuk ditingkatkan, lewat koordinasi, pengajuan proposal, pembimbingan, dan kerjasama dengan berbagai pihak yang memangku kepentingan. Tercapainya 83% (15 SD) yang sudah definitive kepala sekolahnya dan masih 17% (3 SD) menduduki pelaksana tugas kepala sekolah. Tercapainya 38% (65 guru) sudah terpenuhi melalui unsur PNS dan/atau PPPK dan masih terdapat 28% (105 guru) masih guru honorer. Tenaga kependidikan yang meliputi OPS, TAS, Pustakawan dan Penjaga sekolah seluruhnya masih honorer dan berjumlah 20 orang